Pengembangan Agen Virtual Berbasis Telegram Bot Pada SIMANTA Menggunakan Metode Similarity-Sentence Measurement - Tri Ramadani Arjo; Eko Boedhi Santoso (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The use of chatbots is now starting to be widely used to support services from information systems, one of which is SIMANTA. SIMANTA, which is managed by the Department of Business Administration, State Polytechnic of Malang, is used as the management of student final assignments and theses. SIMANTA has been used for 3 years starting from 2019 until now. There are obstacles that have not been overcome by SIMANTA, namely the dependence of students on the SIMANTA admin. With the high demand for using SIMANTA in the Commerce Administration Department, a lot of questions arise about registration, title submissions, guidance information, proposal seminar submissions, proposal seminar schedules, final report exams through social media applications that cannot be handled by the administration. , thus causing problems that cause the information conveyed to be less responsive. This research creates a feature in the form of a chatbot virtual agent on SIMANTA using the Telegram platform. Chatbot is created using BotFather with the name @SIMANTA_BOT. Chatbot utilizes the Similarity-Sentences Measurement method to measure the level of similarity of the questions obtained, and provides responses using the pattern-matching method. With the chatbot feature on SIMANTA, it can help improve services to students, teaching staff, and education staff within the Department of Business Administration.